PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS PENDEKATAN SAINTIFIK PADA MATERI SISTEM PENCERNAAN DI SMA KELAS XI - Arnentis "; Mariani Natalina; Vina Permata Sari (Biogenesis, 2016)
ABSTRACT Research of development has been done which is aim to develop student work sheets based on scientific approach for subjects digestion system on XI grade in senior high school. This research was did in study program of biology and 5 senior high school Pekanbaru on july until august 2015.  Subjects of research were basic competencies 3.7 on digestion system subjects. This research was started by  analyzing the curriculum, syllabus, and work sheets that arranged by Musyawarah Guru Mata Pelajaran (MGMP). And then making the new design of the work sheets according to scientific approach they are 3 lecturers and 2 teachers. Validation aspects that was assessed consist of 3 aspects, which are planning, pedagogic, and the contents. After the validation, the work sheets were fixed according to the inputs and comments from validators and the work sheets part II were produced. After that the work sheets were given limited trial with spreading the students questionnaire responses in 5 senior high school to 17 students on XI grade science class. And next the work sheets were re-revision according to the inputs and comments from the limited trial so that produced the final result of the work sheets. The average of validation results that has been continued develop on digestion system subject are 3.26, 5.50, 3.40. Student responses to the work sheets aspects were 85 with very good category to non-experimental work sheets and 80 with good category to experimental work sheets. the research result showed that development of student work sheets based on scientific approach  for digestion system \subjects has successfully developed using develop model ADDIE with very valid and very good category. Keywords: development, student work sheets, scientific approach, digestion system